Histopathological Records of Oral and Maxillofacial Lesions among Pediatric and Adolescent Patients in Sulaimani Governorate - Dena Nadhim Mohammad; Ban Falih Ibraheem; Balkees Taha Garib; Marwa Abdul-Salam Hamied (MDPI AG, 2022)
Oral and maxillofacial lesions (OMFLs) in pediatrics differ markedly from their adult counterparts in terms of clinical conduct, pathological behavior, and management. This study aims to determine the frequency of OMFLs among pediatric and adolescent patients and to correlate the demographics information to the site, and histopathological findings. Pathological records of pediatric and adolescent patients were retrieved from three major pathological centers in Sulaimani city of Iraq. Demographic information, surgical procedure, anatomical sites, and histopathological diagnosis were recorded. Furthermore, The World Health Organization (WHO) International Statistical Classification of Diseases and Related Health Problems (ICD-10) was used for coding. A Chi-square test was used to find the relation between different variables, and a p-value < 0.05 was considered statistically significant. This study archived 309 (13.3%) out of 2319 pediatric and adolescent patients, with a mean age of 11.04 ± 4.62. Females were more commonly detected (52.8%). The most frequently diagnosed lesions were salivary gland diseases (20.7%), followed by reactive hyperplastic connective tissue (18.4%). A significant relation was found between age groups and diagnostic categories (p = 0.001). The lips were the most commonly detected sites (20.7%). Mucocele was the most frequently seen non-neoplastic lesions (19.4%), followed by pyogenic granuloma (8.7%). Neoplastic lesions revealed predominant hemangioma (3.2%), followed by peripheral ossifying fibroma (1.9%). Traumatic and or reactive lesions were the most commonly reported lesions. Malignant neoplasms can be identified. The current study enabled systematic data recording of pediatric and adolescent patients, encouraging the importance of the oral healthcare system in identifying and managing the problem early in this critical age in this region.